Transfer of surgical knowledge: a continuous challenge - Turina, Marko (SA Heart Journal, 2017)
Cardiac surgery is an expensive method of treatment, and the population’s need will probably never be completely met, even in developed nations, as reflected by recent discussions about limits of care in aged and polymorbid patients. The problem is, of course, much more acute in less developed and developing nations, and their population needs are near impossible to cover. Major surgical associations have only limited funds available, and the transfer of knowledge remains the most efficient way of improving the level of surgical education in these countries, therefore improving care of cardiosurgical patients.